Platelet Count Dynamics after Cardiopulmonary Bypass in Patient Undergoing Single Valve Replacement Surgery - Mahat, Jasmine; Khakural, Prabhat; Bhattarai, Anil; Kunwar, Birendra; Joshi, Ishan (Journal of College of Medical Sciences-Nepal, 2025)
Background Cardiopulmonary Bypass is a standard procedure used during valve surgery to provide circulatory support and allow surgical intervention to replace a malfunctioning or diseased heart valve. Cardiac Surgery involving cardiopulmonary bypass may lead to alterations in platelet count, affecting hemostasis and patient outcome adversely. A study was conducted with the objective of investigating the effect of cardiopulmonary bypass on pre-operative and post-operative platelet count and the factors predicting the circulating platelet count after single valve replacement surgery with the use of cardiopulmonary bypass. Methods An analytical cross-sectional study was conducted Manmohan Cardiothoracic Vascular and Transplant Center, Kathmandu, Nepal from September 2023 to February 2024. All the patients undergoing single valve replacement for rheumatic heart disease were included in the study. The perioperative platelet counts were compared to study the alteration in platelet count dynamics. Data was analyzed using SPSS 16. Results A total of eighty patients were studied. The median platelet count decreased to 170933.75 cells/µL from the pre-operative median platelet count of 235856.25 cells/µL, within 24 hours of operation. Similarly, after 24 hours of operation, the median platelet counts further decreased to 159753.75 cells/µL (n =80). Incidence of thrombocytopenia (<150×104/µL) was observed in 37.5% of patients within 24 hours and 41.3% after 24 hours post-operation. Conclusions The significant decrease in platelet counts following single valve replacement surgery with cardiopulmonary bypass underscores the impact of cardiac surgery on platelet count dynamics. Pre-operative platelet count, age, and bypass time emerged as independent predictors of postoperative platelet count.